Appropriating new communication technologies in migrants’ home communities: A case study from Brazil - Vieira, Kate (AoIR Selected Papers of Internet Research, 2013)
This paper presents preliminary results from an ongoing qualitative study of the impact of migration on the uptake of new technologies in transnational migrants’ home communities, namely Jaú, Brazil. Migration scholars have documented how transnational migration is often undertaken to pay for children’s or family’s formal education. Yet migration itself has its own pedagogy: Many family members learn new technologies to communicate with loved ones abroad. This study traces the uptake of these technological and pedagogical remittances in one community to find that such remittances are often exchanged for cultural capital and career advancement in local economies.